2002
DOI: 10.1002/jsfa.1148
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the volatile components of two cultivars of potato cooked by boiling, conventional baking and microwave baking

Abstract: Tubers of two cultivars (Estima and Maris Piper) of potato were cooked by three different procedures, ie boiling, conventional baking and microwave baking. Peeled and sliced tubers were boiled, while intact potatoes were baked in their skins. Flavour components from the boiled slices and the¯esh of the baked tubers were isolated by headspace adsorption onto Tenax and analysed by gas chromatography±mass spectrometry (GC±MS). For all cooking procedures, Estima gave stronger isolates than Maris Piper. The two mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
27
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…The data is averaged over assessors and replicates. Previous studies have revealed that the sensory quality of cultivars differs (Thybo and Martens 1999;Kaur et al 2002;van Dijk et al 2002;Ochsenbein et al 2008), partially because flavours and taste compounds that are similar in the various potato cultivars differ in intensity Oruna-Concha et al 2002). The PCA bi-plots describing the sensory attributes as a function of applicability confirm a large variation amongst the cultivars (Fig.…”
Section: Selection Of Cultivarsmentioning
confidence: 69%
“…The data is averaged over assessors and replicates. Previous studies have revealed that the sensory quality of cultivars differs (Thybo and Martens 1999;Kaur et al 2002;van Dijk et al 2002;Ochsenbein et al 2008), partially because flavours and taste compounds that are similar in the various potato cultivars differ in intensity Oruna-Concha et al 2002). The PCA bi-plots describing the sensory attributes as a function of applicability confirm a large variation amongst the cultivars (Fig.…”
Section: Selection Of Cultivarsmentioning
confidence: 69%
“…During microwave baking, tuber temperature increases relatively uniformly, with all parts reaching 100°C within a few minutes of each other (Oruna-Concha et al 2002). In contrast to oven baking, the skin remains cooler than the interior of the tuber, due to evaporative cooling.…”
Section: Aromamentioning
confidence: 97%
“…Methyoxypyrazine levels vary with food preparation methods. They have been found in higher amounts in boiled potatoes than in baked potatoes, possibly due to cell damage that results from peeling tubers in preparation for boiling (Oruna-Concha et al 2002). The odor threshold of methoxypyrazines is very low.…”
Section: Aromamentioning
confidence: 99%
See 2 more Smart Citations